The Effect of Sleep, Stress and Physical Activities Toward Obesity in Adolescent Aged 12-18 Years in Yogyakarta City - Abudu, Komaria Ode; Woro Kasmini Handayani, Oktia; Yuniastuti, Ari (Universitas Negeri Semarang, 2019)
Obesity become worrying problem among adolescents, they who are obesed are 80% have the opportunity to experience obesity as adults and have higher risk of serious diseases such as cardiovascular disease, stroke, diabetes, asthma, and some types of cancer. According to the health profile of Yogyakarta Special Province in 2017 the prevalence of obesity was 19.1% occurs in adolescents. The city of Yogyakarta is an area that has many obese people compared to other districts with a prevalence of 4.81%. The purpose of this study was to analyze the effect of sleep patterns, stress and physical activity on the incidence of obesity in adolescents. This research was a quantitative research with a cross sectional approach. The research sample amounted to 109 respondents using the Simple random sampling technique. Instrument used was a questionnaire, observation and documentation. Analysis of calculations in this study used path analysis, it was found the results of sleep patterns with estimates of -0.539 (p = 0.702> 0.05) means that there is an indirect influence on the incidence of Obesity, stress variables indirectly affect the incidence of Obesity through other factors outside the path with coefficients lane is -0.055 (P = 0.963> 0.05) and physical activity variable with an estimate of -0.284 (p = 0.035 <0.05) there is a direct influence on the incidence of Obesity. The results of the study can be a consideration for improving health status by maintaining a healthy lifestyle, regulating sleep patterns, controlling stress and a lot of physical activity.